STRATEGI KOMUNIKASI HUMAS DALAM MENINGKATKAN PUBLIC TRUST DI PERGURUAN TINGGI (Studi Kasus di Universitas Nurul Jadid, Paiton, Probolinggo) - Viki Amalia (JURNAL AL-TANZIM, 2020)
This study aims to analyze and understand the public relations communication strategy in increasing public trust in Nurul Jadid University, Paiton, Probolinggo, East Java. Public trust as the end of public relations communication activities, is very interesting to study, considering the trust will be built if universities have appropriate and effective strategies in carrying out public relations communication activities. This research uses a qualitative approach with case study. Informants in this study consisted of leaders, lecturers, and employees. Data collection techniques are done through interviews, observation and documentation. Data analysis was conducted circularly through stages of data display, data reduction, drawing conclusions. The results showed that; public relations communication strategy in increasing public trust at Nurul Jadid University is done through; Persuasive communication, assertive communication, paradigmatic communication. The implication of this research shows that communication built with the principle of mutual relationship and Islamic values will be able to minimize the miscommunication and misunderstanding between the institution and its people.